Efficacy of probiotic Streptococcus thermophilus in counteracting TGF-β1-induced fibrotic response in normal human dermal fibroblasts - Francesca Lombardi; Francesca Rosaria Augello; Serena Artone; Blerina Bahiti; Jenna Marie Sheldon; Maurizio Giuliani; Maria Grazia Cifone; Paola Palumbo; Benedetta Cinque (BMC, 2022)
Abstract Background Abnormal and deregulated skin wound healing associated with prolonged inflammation may result in dermal fibrosis. Since the current therapeutic strategies revealed unsatisfactory, the investigation of alternative approaches such as those based on the use of specific probiotic strains could provide promising therapeutic options. In this study, we aimed to evaluate whether the lysate from S. thermophilus could antagonize the fibrogenic effects of TGF-β1 in normal human dermal fibroblasts (NHDF). Methods NHDF were exposed to TGF-β1 to establish a fibrotic phenotype. Proliferation rate and cell number were measured using the IncuCyte® Live Cell Imager system and the trypan blue dye exclusion test. Phenoconversion markers (α-SMA and fibronectin) and collagen I levels were assessed by western blot and immunofluorescence. The mRNA levels of TGF-β1 were evaluated by RT-PCR. The Smad2/3 phosphorylation level as well as β-catenin and PPARγ expression, were assessed by western blot. The cell contractility function and migration of NHDF were studied using collagen gel retraction assay, and scratch wound healing assay, respectively. The effects of S. thermophilus lysate, alone or combined with TGF-β1, were evaluated on all of the above-listed parameters and markers associated with TGF-β1-induced fibrotic phenotype. Results Exposure to the S. thermophilus lysate significantly reduced the key mediators and events involved in the abnormal activation of myofibroblasts by TGF-β1 within the fibrotic profile. The S. thermophilus treatment significantly reduced cell proliferation, migration, and myo-differentiation. In addition, the treatment with probiotic lysate reduced the α-SMA, fibronectin, collagen-I expression levels, and affected the collagen contraction ability of activated dermal fibroblasts. Moreover, the probiotic targeted the TGF-β1 signaling, reducing Smad2/3 activation, TGF-β1 mRNA level, and β-catenin expression through the upregulation of PPARγ. Conclusion This is the first report showing that S. thermophilus lysate had a remarkable anti-fibrotic effect in TGF-β1-activated NHDF by inhibiting Smad signaling. Notably, the probiotic was able to reduce β-catenin and increase PPARγ levels. The findings support our point that S. thermophilus may help prevent or treat hypertrophic scarring and keloids.